A hybrid PCA-AHP-Multi-grade Fuzzy approach to assess marketing-based flexibility. Issue 2 (3rd April 2018) - Mishra, Ruchi; Mishra, Onkar Nath
Abstract : Purpose: The purpose of this paper is to propose a novel hybrid approach to assess marketing-based flexibility with respect to its source factors, enablers and attributes. Design/methodology/approach: The study demonstrates an application of a hybrid principal component analysis (PCA)-analytical hierarchical process (AHP)-multi-grade fuzzy approach (MFA) to measure marketing-based flexibility. Using PCA method, attributes, enablers and source factors of marketing-based flexibility were identified and a conceptual model was developed. AHP and MFA were used to compute marketing-based flexibility index. Findings: The proposed approach measures existing level of marketing-based flexibility and therefore it identifies weak areas that should be taken care to improve flexibility. Research limitations/implications: The scope of the study is limited to plant level. The validity of the proposed approach is shown using a case study. For generalisation point of view, the application of this proposed approach should be investigated in a large number of firms in different industrial settings. Practical implications: The study gives a reliable and valid method, which combines both statistical and MCDM techniques to measure existing level of flexibility and identify weak areas for flexibility improvement. Originality/value: The findings provide insight into factors that should be worked upon to improve flexibility.